The Impact of Tourist Satisfaction on Destination Loyalty among European Tourists Visiting Malaysia. - Mahadzirah, Mohamad; Nur Izzati, Ab Ghani (2014)
The purpose of this study was to examine the relationship of tourist satisfaction toward destination loyalty. A survey was carried out at the Kuala Lumpur International Airport (KLIA). A sample of 261 European tourists was obtained at the departure hall using a systematic sampling approach. A Structural Equation Model (SEM) was applied to analyse the data collected. The finding of the study found that tourist satisfaction has a direct positive influence on destination loyalty. The study also found that tourists with a high level of satisfaction are willing to recommend the destination and spread positive word-of-mouth to other people.